The effect of fruits and vegetables changes on the temperature characteristic during microwave heating - ZHANG Ledao; YU Qihui; DING Xiaohang (Shipin yu jixie)
ObjectiveThis study aimed to solve coking scorch caused by excessive local temperature often occurs when microwave heating of fruit and vegetable materials.MethodsA coupling model of electromagnetic-heat conduction with dielectric properties varying with temperature was established, and the correctness of the model was verified by experiments.ResultsWhen the shape is cube, materials with larger dielectric properties are more likely to form a high temperature accumulation zone far from the center, and when the shape is sphere, materials with larger dielectric properties are more likely to form a high temperature accumulation zone in the center. If the size is the same, the temperature uniformity of the material with smaller dielectric properties is higher, and the temperature uniformity is increased by 43.8% when the dielectric constant is reduced by 24.8%.ConclusionThe temperature distribution uniformity of the material can be effectively controlled by adjusting the dielectric characteristics and size of the material.